Limits to the reproductive success of two insect parasitoid species in the field. Issue 11 (1st November 2013) - Segoli, Michal; Rosenheim, Jay A.
Abstract : Debates on the relative importance of different factors in limiting the realized fitness of insect parasitoids and herbivores have continued for decades. One major reason for the duration of these debates is the paucity of empirical evidence regarding the reproductive success of minute insects under field conditions. We used a novel technique to estimate lifetime reproductive success in two Anagrus spp. parasitoids, whose hosts are eggs of leafhoppers that feed on grape leaves. Females were collected soon after they died naturally, and the number of eggs in their ovaries was counted. We used these data to estimate the lifetime oviposition success of individual females. We found that more than 10% of females from the field exhausted their entire supply of eggs before they died. The lifetime reproductive success of females was positively related to their body size and was higher at field sites with more abundant hosts, although we could not rule out a causal role for other site‐specific factors. In addition, we found that females from habitats rich with hosts emerged with more eggs, suggesting that they might be adapted to local conditions. The results are consistent with theoretical predictions from models considering the risk of egg limitation.